2012
DOI: 10.1093/rheumatology/kes223
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum uric acid levels on the risk of all-cause and cardiovascular mortality

Abstract: Individuals with SUA levels at either extremes are at higher risk for all-cause and cardiovascular mortality. SUA levels of 0.30-0.41 mmol/l were associated with the lowest mortality rate and should be regarded as optimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
115
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 32 publications
8
115
2
9
Order By: Relevance
“…Our study did not aim to assess the relationship between the change of SUA and mortality risks. A single measurement of SUA to predict outcomes was a simplified and practical approach, similar to what was done by previous researchers 5, 6, 7, 8, 10, 11. Information on diuretics and urate‐lowering agents was lacking in our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our study did not aim to assess the relationship between the change of SUA and mortality risks. A single measurement of SUA to predict outcomes was a simplified and practical approach, similar to what was done by previous researchers 5, 6, 7, 8, 10, 11. Information on diuretics and urate‐lowering agents was lacking in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Uric acid, the final product of purine degradation in humans, mediates proinflammatory endothelial dysfunction and is associated with greater risks for CVD events 3, 4. Although a wealth of research has reported that an elevated serum uric acid (SUA) level >7 mg/dL independently predicts all‐cause and CVD‐related mortality in middle‐aged adults,5, 6, 7 studies linking hyperuricemia to mortality risks in the elderly population are conflicting and inconclusive 8, 9, 10, 11, 12, 13, 14. Earlier studies indicate that hyperuricemia is associated with increased risks of death from any causes and CVD‐related mortality in older adults 8, 9, 10, 11.…”
mentioning
confidence: 99%
“…A large prospective study in Taiwan reported that sex-and ageadjusted hazard ratios of uric acid levels for all-cause and cardiovascular mortality were increased not only for elevated uricemia, but also for levels lower than 5 mg/dl [25]. An as yet unpublished work among Turks from applicants of a tertiary hospital showed inverse association of serum uric acid with adverse outcomes, consistent with involvement of uric acid mass in autoimmune activation.…”
Section: Journal Of Clinical and Cellular Immunologymentioning
confidence: 86%
“…Не-обходимо отметить, что различные варианты патоло-гических суточных профилей АД встречались не толь-ко у пациентов с АГ, но также и у нормотоников. По дан-ным литературы профиль АД типа нондиппер или найтпикер напрямую связан с поражением органов-мишеней: увеличением индекса массы миокарда левого желудочка, ухудшением функционального состояния по-чек, высокой частотой развития цереброваскулярных осложнений в сравнении с пациентами с нормальным снижением АД во время сна [1,5]. В некоторых иссле-дованиях указывается, что чрезмерное снижение АД в ночное время ассоциировано с риском развития ате-росклеротического поражения сонных и коронарных ар-терий, возможным ухудшением мозгового кровооб-ращения и ранним развитием безболевой ишемии мио- The glomerular filtration rate in patients with gout Фильтрационная способность почек у больных подагрой карда [11], что свидетельствует о необходимости более тщательного мониторинга больных подагрой на пред-мет своевременной диагностики скрытой АГ и пора-жения органов-мишеней для предотвращения разви-тия сердечно-сосудистых катастроф.…”
Section: Discussionunclassified
“…
Ведущей причиной сердечно-сосудистых ослож-нений у больных подагрой является артериальная ги-пертония (АГ), частота которой достигает 47-72% [1][2][3]. Нарастание концентрации мочевой кислоты (МК) на 1 мг/дл вызывает повышение уровня систо-лического артериального давления (АД) на 30 мм рт.
…”
unclassified